(NwIOLON^ELX (BSolo . (NaLHIMIQ MUZYKI (B85 (NLETI@s (NMONOGRAFIQs - (NwASILXEWA a(B.s ((NmOSKWAs, 2019)
(NkNIGA wIOLON^ELX (BSolo (NaLHIMIQ MUZYKI WYHODIT W SWET K (B85 (NLET@ WYDA@]EJSQ WIOLON^ELISTKI NARODNOJ ARTISTKI ROSSII PROFESSORA aLLY wASILXEWOJ (B(1933-2018).s
Keywords: (NMONOGRAFIQs